Ad-hoc, mobile, and wireless networks : 16th International Conference on Ad Hoc Networks and Wireless, ADHOC-NOW 2017, Messina, Italy, September 20-22, 2017, Proceedings /: 16th International Conference on Ad Hoc Networks and Wireless, ADHOC-NOW 2017, Messina, Italy, September 20-22, 2017, Proceedings. (2017) - Unknown
No abstract available